(untitled) (Linguostylistic Studies, 2016)
The article focuses on the analysis of the verbalization peculiarities of the ideologeme «the Ukrainian Language» which have been identified in the course of exploring the scientific communicative activities at a Round Table Discussion held at M. V. Lomonosov Moscow State University. The topic of the Round Table Discussion was «The Russian Language under Conditions of Language and Cultural Polyphony». The verbatim records of the Round Table Discussion has become the material of the research, which present live scientific speech of the Russian scientists recorded in the verbatim reports. The research offers insights into the specific affective, idealogized «pseudoscientific communication». This «pseudoscientific communication» is greatly dependent on the expression and verbalization of feelings, emotions, estimations, ego-thoughts, «ideological myths» aimed at the humiliation of Ukraine, the Ukrainian language, the Ukrainians as the nation, the verbalization of disrespect, mockery and sarcasm. The scientists’ speech is characterized by the violation of a scientific argumentation, etiquette, correctness. All these things do not comply with the scientific style norms, but represent the ideological rhetoric, appealing to «their» own history, while the history of the Ukrainian nation has been misrepresented and falsified. The allusion has been created on the very fact that there was no russification, that there were no prohibitions of the Ukrainian language, culture, and the Ukrainian state as a whole. The author draws the conclusion that, in fact this ideology has been cultivated for centuries and penetrated even the scientific discussions. Key words: Russian scientific discourse, live speech, scientific communication, ideologem, the Ukrainian language. References